Task complexity as a moderator of goal effects: A meta-analysis. - Wood, Robert E.; Mento, Anthony J.; Locke, Edwin A. (Journal of Applied Psychology, 1987)
Much evidence exists that supports the use of goal setting as a motivational technique for enhancing task performance; howevei; little attention has been given to the role of task characteristics as potential moderating conditions of goal effects. Meta-analysis procedures were used to assess the moderator effects of task complexity for goal-setting studies conducted from 1966 to 1985 (n = 125). The reliability ofthe task complexity ratings was .92. Three sets of analyses were conducted: for goaldifficulty results (hard vs. easy), for goal specificity-difficulty (specific difficult goals vs. do-best or no goal), and for all studies collapsed across goal difficulty and goal specificity-difficulty. It was generally found that goal-setting effects were strongest for easy tasks (reaction time, brainstorming), d = .76, and weakest for more complex tasks (business game simulations, scientific and engineering work, faculty research productivity), d = .42. Implications for future research on goal setting and the validity of generalizing results are discussed.